Assessment of agricultural information needs in African, Caribbean and Pacific (ACP) States for CTA’s Products and Services: Country Study: Mozambique - Ribeiro, Vera; Norfolk, Simon; Terra Firma Lda (Technical Centre for Agricultural and Rural Cooperation, 2006)
The objectives of this study are to develop a strategy for CTA’s approach to post-conflict countries, to improve the effectiveness of CTA’s support for post-conflict countries and to compile baseline data on the status of ICM and ICTs in agriculture..